2016
DOI: 10.2176/nmc.oa.2015-0341
|View full text |Cite
|
Sign up to set email alerts
|

Early Cerebral Circulation Disturbance in Patients Suffering from Severe Traumatic Brain Injury (TBI): A Xenon CT and Perfusion CT Study

Abstract: Traumatic brain injury (TBI) is widely known to cause dynamic changes in cerebral blood flow (CBF). Ischemia is a common and deleterious secondary injury following TBI. Detecting early ischemia in TBI patients is important to prevent further advancement and deterioration of the brain tissue. The purpose of this study was to clarify the cerebral circulatory disturbance during the early phase and whether it can be used to predict patient outcome. A total of 90 patients with TBI underwent a xenon-computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Ischemia is defined as the lack of cerebral blood flow (CBF), specifically when the CBF is under 20 ml/100 g/min (Baron, 2001). There are many factors that can contribute to ischemic conditions in the brain after TBI, including increased intracranial pressure, cerebral edema, traumatic vasospasms, and microcirculation disruption (Honda et al, 2016). In addition, the shearing forces described previously can contribute to the capillary disruption and vasoconstriction by tearing the microvasculature, causing the decreased CBF observed in TBI (Bouma, Muizelaar, Bandoh, & Marmarou, 1992;Bouma, Muizelaar, Choi, Newlon, & Young, 1991;DeWitt & Prough, 2009;McKee & Daneshvar, 2015).…”
Section: Ischemiamentioning
confidence: 99%
“…Ischemia is defined as the lack of cerebral blood flow (CBF), specifically when the CBF is under 20 ml/100 g/min (Baron, 2001). There are many factors that can contribute to ischemic conditions in the brain after TBI, including increased intracranial pressure, cerebral edema, traumatic vasospasms, and microcirculation disruption (Honda et al, 2016). In addition, the shearing forces described previously can contribute to the capillary disruption and vasoconstriction by tearing the microvasculature, causing the decreased CBF observed in TBI (Bouma, Muizelaar, Bandoh, & Marmarou, 1992;Bouma, Muizelaar, Choi, Newlon, & Young, 1991;DeWitt & Prough, 2009;McKee & Daneshvar, 2015).…”
Section: Ischemiamentioning
confidence: 99%
“…A literature research including the terms "traumatic brain injury" and "perfusion CT" or "perfusion computed tomography" returned 185 results. Critical screening of the abstracts selected 18 papers that were considered as pertinent and relevant to this review and therefore they were analyzed and discussed in detail [16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Table 1 illustrates the studies' characteristics and main findings.…”
Section: Perfusion Ct and Traumatic Brain Injurymentioning
confidence: 99%
“…The relationship between perfusion CT findings and invasive ICP and calculated CPP has been more recently investigated by Honda et al [27]. The perfusion maps of 25 patients with severe TBI and ICP monitor were obtained with , while in patients with cerebral hypertension, the CBF negatively correlated with the CPP value (disrupted autoregulation).…”
Section: Cerebral Perfusion Pressure and Perfusion Ctmentioning
confidence: 99%
“…Experimental and clinical studies have shown that early blood-brain barrier (BBB) breakdown (Su et al, 2015; Tomkins et al, 2008; Yang et al, 2013) and hypoperfusion (Honda et al, 2016; Kaloostian et al, 2012; Kelly et al, 1997; Li et al, 2012; Stein et al, 2011; Ziegler et al, 2016) after TBI are associated with poor neurological outcome, indicating the detrimental role of BBB dysfunction and circulatory derangement in the pathophysiology of TBI. These vascular and hemodynamic abnormalities, which could last years following the trauma (Korn et al, 2005; Newsome et al, 2012; Tomkins et al, 2008), are not exclusively restricted within the ipsilateral hemisphere, but are heterogeneously present in both hemispheres of the injured brain (Beaumont et al, 2000; Dietrich et al, 1998; Hayward et al, 2011; Hendrich et al, 1999; Kim et al, 2010; Park et al, 2009; Pasco et al, 2007; Su et al, 2015), suggesting a dynamic pathophysiological evolvement in both time and space.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic changes in a widespread area of cerebral tissue may reflect the brain remodeling in response to the cell intervention. To date, however, most research has primarily focused on either BBB leakage (Su et al, 2015; Tomkins et al, 2008; Wei et al, 2012; Yang et al, 2013) or perfusion deficits (Chen et al, 2013; Honda et al, 2016; Kaloostian et al, 2012; Kelly et al, 1997). There are few studies (Li et al, 2016; Lin et al, 2012) documenting the dynamic relationship between the degree of BBB damage and perfusion status post-injury, especially within a long period of time post-TBI and in a broad area of cerebral tissue.…”
Section: Introductionmentioning
confidence: 99%